The Cultural of Pu-Cha Drums of Thai-Yong in Baan Don-Luang, Mae Rang Sub-District, Pa Sang District, Lamphun Province: The Cultural of Pu-Cha Drums of Thai-Yong in Baan Don-Luang, Mae Rang Sub-District, Pa Sang District, Lamphun Province - Subphasri, Poramase; Jaikum, Krerkpong (Journal of Graduate MCU KhonKaen Campus, 2022)
The objectives of the research on the cultural of Pu-Cha drums of the Thai Yong people at Baan Don Luang, Mae Rang Sub-district, Pa Sang District, Lamphun Province, were as follows: (1) To study the musical characteristics of Pu-Cha drums, Baan Don Luang, Mae Rang Sub-district, Pa Sang District, Lamphun Province. (2) To study the relationship of Pu-Cha drums to the culture of the Thai-Yong community in Baan Don Luang, as well as other relevant community cultures. The methodological approach used in this research was qualitative; data was collected through both structured and unstructured interviews. The study found that the Pu-Cha drums of Thai-Yong in Baan Don Luang are an ancient musical culture that is the legacy of generations, and the treasure of the community. The instruments accompanying with Phu-Cha drums are several types of Lanna instruments, such as Pu-Cha drums, Ta lod pode drum, Nae, cymbals, and gong. When mixing the band, the role and function of each instrument is assigned, Phu-Cha drums play as the leading instrument while the accompanying musical instruments are gongs, cymbals, and Ta lod pode drums. The rhythm of Pu-cha drumming includes the melody of Seur Kop Tu, Sao Lap Ter melody, Lhong Nan melody, and Fad Sae melody, and the melody of the Tung Nong drum has been added to the present. There are 9 musicians in Pu-Cha drums band, who are members of the Baan Don Luang community and villagers in nearby communities. Pu-Cha drums in Baan Don Luang represent beliefs and rituals. In addition to that, Pu-Cha drums play a role in cultural society in various areas, including the role of communication within the community, respect for Buddhist monks, and the role of preserving the local cultures of other communities.